ANALISA FUNDAMENTAL PERGERAKAN SAHAM INDIVIDUAL SUB SEKTOR TELEKOMUNIKASI TAHUN 2020 - Hikmah Putri, Nurul; Ramadani, Amelia; Nofita Sari, Arnes (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
A Fundamental influence on stock prices. Fundamental factors used are current ratio, DER and ROA, while the technical factors used are INDEX and trading volume. The results of the test on the research conducted, it can be concluded that, the Price of the stock on the company's telecommunications sector listed on the Indonesia stock Exchange 2020 influenced from DER, and ROA. While the CR, the composite Stock Price Index, and the Volume of trade does not affect the stock Price. But CR, DER,ROA, composite Stock Price , trading volume simultaneously affect Stock Prices in the sector.